Analisis motivasi belajar bahasa indonesia tema makanan sehat secara daring di rumah pada peserta didik kelas V sekolah dasar - Ningrum, Ayu Puspita; Sriyanto, Muhammad Ismail; Sukarno, Sukarno (Universitas Sebelas Maret, 2021)
The purpose of this study was to analyze the motivation to learn the theme of healthy food learning Indonesian online in fifth grade Mangkuyudan elementary school. The method used in this research is qualitative with a phenomenological approach. Data collection was carried out by means of questionnaires, interviews and documentation. Data analysis in this study used interactive analysis by Miles & Huberman. The analysis includes data collection, data reduction, data presentation, and drawing conclusions. The results of this study were that the learning motivation students of Mangkuyudan elementary school was categorized into five. The very high category was 7.14%, the high category was 32.14%, the medium category was 28.57%, the low category was 25%, the very low category was 7.14%. The influencing factors are students 'aspirations, students' abilities such as being diligent in learning and collecting assignments on time, the condition of physical students and the availability of telephones for online learning, and the teacher's efforts to provide motivation. The conclusion of this study is that students' learning motivation is in the high category. The form of motivation to learn Indonesian that students get from teachers online is praise, giving tests, and giving grades.